Pengaruh Media Sosial dan Literasi Ekonomi terhadap Minat Berwirausaha Mahasiswa - Mualif Hari Wahyudi; Kapriani, Aldia; Sumarno; Saybrus, Hardisem (Jurnal Ilmu Sosial dan Humaniora, 2024)
This study aims to determine how much influence social media and economic literacy have on the entrepreneurial interest of students of the Faculty of Teacher Training and Education, Riau University. This research is included in quantitative research. The population in this study was 1351 with a research sample of 93 students. Sampling technique using random sampling. Data collection techniques used are questionnaires and tests through google form. This study uses descriptive analysis, multiple linear analysis, normality test, linearity test, heteroscedasticity test, multicollinearity test, T test, F test and coefficient of determination test. The results of this research show social media and economic literacy together (simultaneously) have a positive and significant effect on the entrepreneurial interest of students of the faculty of teacher training and education, University of Riau. The results of the analysis of independent variables namely social media and economic literacy have a joint contribution of 0,494. This means that all independent variables namely social media and economic literacy have a joint contribution of 49,4% to the interest in entrepreneurship while the remaining 50,6% is influenced by other variables not discussed in this study.